Health benefits and application of polysaccharides from Polygonatum cyrtonema Hua - Huang, Xiaoyan; Chen, Xingying; Jiang, Faming (Frontiers in Pharmacology, 2025)
Polygonatum cyrtonema Hua is a herbaceous plant renowned for its dietary and medicinal properties. Research has demonstrated that the polysaccharides derived from P. cyrtonema Hua exhibit significant anti-inflammatory, antioxidant, immunomodulatory, anti-cancer, anti-fatigue, anti-depression, and anti-obesity activities, as supported by both in vitro studies and animal experiments. They also help balance intestinal flora, regulate blood sugar, and prevent cardiovascular disease and Alzheimer’s disease. These effects are mediated through various signaling pathways, such as the mitogen-activated protein kinase, nuclear factor kappa-B, and nuclear factor erythroid 2-related factor 2/heme oxygenase-1 antioxidant signaling. The versatility of polysaccharides from P. cyrtonema Hua extends to applications in food and medicine, promoting overall health and wellbeing. This article reviews the pharmacological activities of polysaccharides in P. cyrtonema Hua and the factors affecting their content and structure, with particular emphasis on the Paozhi processing technique. This review highlights the multifaceted health benefits of these polysaccharides, underscoring their potential as functional food and therapeutic agents. Future research could focus on clinical studies, bioavailability, pharmacokinetics, and structure-function relationship to further validate these health claims and explore the underlying mechanisms of its bioactive compounds.